Cloning, expression and functional study of specific DNA markers for Salmonella Typhi / Noradilin binti Abdullah - Abdullah, Noradilin (2013)
ST332 is a 332 bp gene marker used in a patented Salmonella kit for detection of foodborne pathogen, Salmonella Typhi. As the gene is specific in DNA based detection by using polymerase chain reaction (PCR), its specificity in immunoassay is studied. For this purpose, an expression system of the gene is constructed and the expressed recombinant ST332 protein is tested for reactivity by hybridizing it towards typhoid patients sera through dot blotting. Initially, the DNA fragment was amplified with PCR and cloned into pGEX-4T-1 plasmid vector and transformed into E. coli BL21. Sequencing of the 332 bp fragment identified it as a hypothetical protein of S. Typhi strain CT18 (STY4528), a gene located on Salmonella Pathogenicity Island 7 (SPI-7) in Salmonella. The recombinant protein was expressed by induction with IPTG and extracted with NP-40 buffer. Analysis of the recombinant protein with dot blot immunoassay revealed weak affinity towards typhoid patients pooled-sera thus made it unreactive as an antigen. In another approach of obtaining specific S, Typhi antigen, a library of Novablue (E. coli DE3) cells expressing short fragment (150 – 300 bp) of S. Typhi genomic DNA was constructed by using Novatope Cloning System (Novagen). Here, about 700 clones were produced and the clones were pre-screened for reactivity towards typhoid patients’ pooled-sera by colony blot immunoassay. Clones that showed higher reactivity than negative control were selected and further screened with dot blot immunoassay. Here, about 20 clones showing strong signals on dot blot were selected and further analyzed with ELISA immunoassay. Twice of the assays revealed that at least 3 clones (D1, G35 and I3) were highly reactive towards the typhoid patients antisera with at least 2-fold titre compared to typhoid negative sera.